Peran Biang Kampung pada Ibu Hamil dan Pasca Melahirkan di Desa Motoling Dua Kecamatan Motoling - Zevania Kordak; Maria Heny Pratiknjo; Titiek Mulianti (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
Village midwife is a community figure who is still trusted to accompany pregnant women, the community feels comfortable with the assistance of biang kampung. This study aims to determine the role of biang kampung in pregnant women and postpartum in Motoling Dua Village, Motoling District. This study used qualitative descriptive research with data collection techniques in the form of observation, interviews and documentation. From the results of the study, it was obtained that biang kampung is still trusted to accompany pregnant women and postpartum where the community in Motoling Dua Village feels more comfortable and safer with the role of biang kampung given to pregnant women to help with childbirth until postpartum. The results of the study also found that biang kampung has begun to work with existing medical personnel to improve maternal health services. Although in this day and age modern medicine is increasingly sophisticated, public trust in biang kampung still exists and the community hopes that biang kampung will always be there to accompany pregnant women before and after childbirth.